Staff and Facility Utilization in Direct Patient Transfer to the Comprehensive Stroke Center: Testing a Real-Time Location System for Automatic Patient Pathway Characterization - Moreira, Tiago; Furnica, Alexander; Daemen, Elke; Mazya, Michael V.; Sjöstrand, Christina; Kaijser, Magnus; Loenen, Evert van (Frontiers in Neurology, 2021)
Introduction: Starting reperfusion therapies as early as possible in acute ischemic strokes is of utmost importance to improve outcomes. Comprehensive stroke centers (CSC) can use surveys, shadowing personnel or perform journal analysis to improve logistics, which can be labor intensive, lack accuracy and disturb the staff by requiring manual intervention. The aim of this study was to measure transport times, facility usage, and patient-staff co-localization with an automated Real-Time Location System (RTLS). Patients and methods: we tested infrared detection of patient wristbands and staff badges in parallel with a period when stroke patients’ triage was changed from admission to the emergency room (ER) to direct admission to neuroradiology. Results: In total 281 patients were enrolled. In 242/281 (86%) of cases, stroke patient logistics could be detected. Consistent -patient-staff co-localizations were detected in 177/281 (63%) of cases. Bypassing the ER led to a significant decrease in median time neurologists spent with patients (from 15 to 9 min) but to an increase of the time nurses spent with patients (from 13 to 22 min; P = 0.036). Ischemic stroke patients used the most staff time (median 25 min) when compared to hemorrhagic stroke patients (median 13 min) and stroke mimics (median 15 min). Discussion: time spent with patients increased for nurses but decreased for neurologists after direct triage to a CSC. While lower in-hospital transport times were detected, time spent in neuroradiology (CT room and waiting) remained unchanged. Conclusion: RTLS could be used to measure time stamps in stroke pathways and assist in staff allocation.